A numerical investigation of coorbital stability and libration in three dimensions - Morais, M. H. M. [UNESP]; Namouni, F. (Springer, 2016)
Motivated by the dynamics of resonance capture, we study numerically the coorbital resonance for 0 <= I <= 180 degrees inclination in the circular restricted three-body problem. We examine the similarities and differences between planar and three dimensional coorbital resonance capture and seek their origin in the stability of coorbital motion at arbitrary inclination. After we present stability maps of the planar prograde and retrograde coorbital resonances, we characterize the new coorbital modes in three dimensions. We see that retrograde mode I (R1) and mode II (R2) persist as we change the relative inclination, while retrograde mode III (R3) seems to exist only in the planar problem. A new coorbital mode (R4) appears in 3D which is a retrograde analogue to an horseshoe-orbit. The Kozai-Lidov resonance is active for retrograde orbits as well as prograde orbits and plays a key role in coorbital resonance capture. Stable coorbital modes exist at all inclinations, including retrograde and polar obits. This result confirms the robustness the coorbital resonance at large inclination and encourages the search for retrograde coorbital companions of the solar system's planets.
Keywords: Co-orbital resonance; Resonance; Three-body problem; Retrograde resonances; Kozai-Lidov mechanism; Resonance trapping